Prinsip Menilai dan Menentukan Media Pembelajaran - Rusdiono (Institut Agama Islam Sahid (INAIS) Bogor, 2020)
Teachers should plan and implement learning activities in the classroom using the media. Therefore, the learning process will be more effective and efficient. The use of media can help the goal of learning achievement. However, choosing the right media to be used in learning is not easy. The selection of media requires certain principles in order to provide appropriate media. Before determining instructional media, teachers should consider the philosophical, psychological, and sociological aspect in selecting and using instructional media. Media selection should also refer to three main principles. They are the principles of effectiveness and efficiency, the principle of relevance, and the principle of productivity. The selection of instructional media should also consider several criteria. First, in accordance with the purpose of learning. Media is selected based on predetermined instructional goals that generally refer to one or a combination of two or three domains: cognitive, affective, and psychomotor.Second, it support the content of the lesson. Third, it practical, flexible, and durable. Fourth, teachers can use it. Fifth, suitable for student. Sixth, good quality.